O prescrito e o real da atividade dos psicólogos organizacionais: uma análise das dramáticas do uso de si dos psicólogos de empresas de terceirização - Silva, Vanessa Nascimento (2013)
The present scenario of the world of work, with its global competitiveness and the increasing precariousness of work, it was the starting point for this research that aimed to analyze the activity of psychologists organizational in outsourcing companies, relating them with the characteristics of the contemporary context. Based on the theory of the ergology, of the Yves Schwartz, whose the fundamental concept, that there is a prescribed work (which is requested, by another person, that there is not the professional) and real work (which is how the work activity actually happens), and among them there is always a distance. This fact causes the subject to perform a management use of himself, by himself and others, which are implicate in their own subjectivity and values, as well as the values and norms of the society itself. That process management, Schwartz appoints dramatic use of self. Then, a survey was conduct socio historical qualitative, which aimed to identify the prescribed activity psychologists on such companies, as well as analyze how these professionals perform their activity before the real is presented to them, pointing here evidence of the precarious aspects that compose their work activity. It was identified, also, the management that the subject does himself, by himself and by others, in order to relate the re-norms that underlie the actual activity of psychologists with the values and standard that cross the subject himself and society contemporary work. Came up as a result of the fact that the activities prescribed for these professionals are still primarily recruitment and selection of staff. Such activities are constantly transfixed by the logic of precariousness, which refers to the high speed of the process, the recovery by productivity, the search for the lowest cost and highest profit, regardless of commitment to human. It was noted that psychologists are inserted in the surveyed companies use management itself, emphasizing the logic of the market in their choices, and that their values sometimes are consistent with this logic. Faced with such evidence, reiterated the need to recover a commitment most critical action of psychologists, recognizing the priority of commitment to the human being, wherever they operates.